Generalized linear mixed models can detect unimodal species-environment relationships - Jamil, Tahira; ter Braak, Cajo J.F. (PeerJ, 2013)
Niche theory predicts that species occurrence and abundance show non-linear, unimodal relationships with respect to environmental gradients. Unimodal models, such as the Gaussian (logistic) model, are however more difficult to fit to data than linear ones, particularly in a multi-species context in ordination, with trait modulated response and when species phylogeny and species traits must be taken into account. Adding squared terms to a linear model is a possibility but gives uninterpretable parameters. This paper explains why and when generalized linear mixed models, even without squared terms, can effectively analyse unimodal data and also presents a graphical tool and statistical test to test for unimodal response while fitting just the generalized linear mixed model. The R-code for this is supplied in Supplemental Information 1.
Keywords: Environmental gradient; Testing unimodal response; Niche theory; Generalized linear mixed model; Gaussian logistic model